Analysis of critical factors causing project close out delay at PT. Gas Mandiri - Wiji Seno, Gunar; Firman, Aries F (The Indonesian Journal of Business Administration, 2018)
Abstract. Project close out in most cases was not really considered as important as executing, completing and delivering process to the end user of the intended facilities or services as objectives of the project, therefore many projects were experienced delay in this process. It is important for project practitioner and all stakeholders to understand overall project process, especially knowing the expected complete final deliverables, how to ensure and assure that it can be accomplished within stipulated project timeframe and therefore always â€œbegins with the end in mindâ€ is crucial. And in order all activities performed could beneficial, it is essential to always renew the intention only for the Almighty God. PT. Gas Mandiri (GM) is an energy company located in Middle East that primarily produces Liquefied Natural Gas (LNG). The company develops and operates offshore and onshore production facilities for extraction and processing products before it exported in addition of supplying domestic markets. The company developed and executed greenfield and brownfield projects to enhance and sustain production of the products. This thesis is focused on finding critical factors of project close out delay in the Operation Project Engineering Department. Compiling and analyzing secondary data and primary data using qualitative approach and referring to project management standard/guide and internal company process/procedure, it was found that four major project management knowledge area which are project human resources management, project integration management, project time management and project stakeholders management were critical factors contributing to delay of the project close out. Many process involved, lack of priority in planning, share/lack of resource, lack of competency/training, ineffective Contractor selection and doubtful of established timeframe measurement were the root cause of the delay. In the end of the thesis, based on cheese protective barrier model, the solutions and recommendations segregated/grouped and action plan defined to overcome and anticipate project close out delay issues in the PT. Gas Mandiri.Keywords: Project Management, Project Close Out, Close out Delay, Critical factors